M. ALI AL-SHABUNI INTERPRETATION OF AYAT AL-QUR'AN WHICH IMPLEMENTS TOLERANCE - komarudin, didin (ASWAJA: Jurnal Pendidikan dan Keislaman, 2024)
Indonesia, a country that has various ethnicities, nations, cultures, and even religions, should Indonesian citizens have a very high attitude of tolerance. However, the reality that occurs in this land of Indonesia is very contrary to all teachings in the Koran (Islam) or from outside religions other than Islam. Indeed, it is very unfortunate that this country full of diversity can be said that conflicts often occur due to the intolerance of certain individuals. Even at this time, there are still cases that stem from a lack of tolerance among religious people, especially in Indonesia. This research basically wants to convey a discussion, including: What is the meaning of tolerance (tasamuh), how is the interpretation of tolerance according to M. Ali al-Shabuni in the interpretation of Shafwat Al-Tafaasir and how to implement tolerance according to al-Shabuni. Tolerance is letting go, generosity and grace. Tolerance means respecting and respecting one's beliefs, beliefs, culture, ethnicity or other groups with patience, awareness and sincerity. Tolerance does not mean justifying the beliefs or beliefs of others, but respecting and respecting the human rights of others, even if these things differ from our beliefs. This research uses qualitative research with analytical descriptive method. Data collection was carried out by means of the Library Research (literature study). Regarding library research, the researcher took two data sources, namely the primary data source in the form of the book of interpretation of Shafwat al-Tafaasir by M. Ali al-Shabuni, and secondary sources in the form of books and other literature that support the discussion of tolerance. The results of this study indicate that, tolerance is defined as the giver of freedom to fellow human beings or fellow citizens to practice their beliefs, or organize their lives and determine their own lives. And al-Shabuni's interpretation of the verses related to tolerance does not contradict what has been taught by the Prophet, and also the previous' Ulama. And as for the way to implement tolerance according to Islam, there are three elements that cover all social-societal values, namely: Respecting the beliefs of others, Open Minded (having an open mind) and understanding each other.